2017
DOI: 10.5194/bg-14-2781-2017
|View full text |Cite
|
Sign up to set email alerts
|

Soil nitrogen oxide fluxes from lowland forests converted to smallholder rubber and oil palm plantations in Sumatra, Indonesia

Abstract: Abstract. Oil palm (Elaeis guineensis) and rubber (Hevea brasiliensis) plantations cover large areas of former rainforest in Sumatra, Indonesia, supplying the global demand for these crops. Although forest conversion is known to influence soil nitrous oxide (N 2 O) and nitric oxide (NO) fluxes, measurements from oil palm and rubber plantations are scarce (for N 2 O) or nonexistent (for NO). Our study aimed to (1) quantify changes in soil-atmosphere fluxes of N oxides with forest conversion to rubber and oil pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
62
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 46 publications
6
62
2
1
Order By: Relevance
“…Although oil palm is of economic value to farmers and the local regions in which it is grown, it has received environmental and social criticism, often being held responsible for deforestation (Wicke et al, 2011;Vijay et al, 2016;Gatto et al, 2017), biodiversity loss (Fitzherbert et al, 2008;Koh and Wilcove, 2008;Wilcove and Koh, 2010;Carlson et al, 2012;Krashevska et al, 2015), decreased soil carbon stocks (Guillaume et al, 2015Pransiska et al, 2016), and increased greenhouse gas emissions (Allen et al, 2015;Hassler et al, 2017). Similarly, rubber plantations have environmental impacts such as reducing the soil infiltration capacity, accelerating soil erosion, increasing stream sediment loads (Ziegler et al, 2009;Tarigan et al, 2016b), and decreasing soil carbon stocks (Ziegler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although oil palm is of economic value to farmers and the local regions in which it is grown, it has received environmental and social criticism, often being held responsible for deforestation (Wicke et al, 2011;Vijay et al, 2016;Gatto et al, 2017), biodiversity loss (Fitzherbert et al, 2008;Koh and Wilcove, 2008;Wilcove and Koh, 2010;Carlson et al, 2012;Krashevska et al, 2015), decreased soil carbon stocks (Guillaume et al, 2015Pransiska et al, 2016), and increased greenhouse gas emissions (Allen et al, 2015;Hassler et al, 2017). Similarly, rubber plantations have environmental impacts such as reducing the soil infiltration capacity, accelerating soil erosion, increasing stream sediment loads (Ziegler et al, 2009;Tarigan et al, 2016b), and decreasing soil carbon stocks (Ziegler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Functional water flow regulation by a watershed reduces flood peaks by moderating direct runoff (Le Maitre et al, 2014;Ellison et al, 2017) via soil water infiltration through the soil surface and percolation through the soil profile. This vertical movement of water through the soil determines how much water flows as direct runoffs and how much reaches the water table where it is sustained as baseflow or groundwater (Hewlett and Hibbert, 1967;Bruijnzeel, 1990;Le Maitre et al, 2014;Tarigan et al, 2016b). Forest vegetation provides organic matter and habitat for soil organisms, thereby facilitating higher levels of infiltration than other land uses (Hewlett and Hibbert, 1967).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrous oxide is a gaseous intermediate in the reaction sequence of denitrification and a by-product of nitrification that leaks from microbial cells into the soil and ultimately to the atmosphere (Bouwman 1998, Smith et al 2003 (Melling et al 2007, Aini et al 2015, Sakata et al 2015, Hassler et al 2017 and some are based on very short sampling periods (Ishizuka et al 2005, Banabas 2007, Fowler et al 2011. Aini et al (2015) observed highly elevated emission rates following N fertilization in a plantation cultivated on mineral soil in Jambi, Sumatra.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of forests to agricultural plantations may further contribute substantially to non-CO 2 GHG emissions 19 , but field quantifications of methane (CH 4 , global warming potential, GWP of 25 2,20 ) and nitrous oxide (N 2 O, GWP of 298 2,20 ) emissions in oil palm plantations are so far limited [16][17][18]21,22 . The net global warming potential (GWP net ) 23 , which includes the net ecosystem exchange (NEE) of CO 2 fluxes as well as soil CH 4 and N 2 O fluxes, has previously not been assessed for oil palm plantations, despite their rapid expansion across the tropics.…”
mentioning
confidence: 99%